The Relationship Between Knowledge Levels and Behavior with Anxiety Among Families of Stroke Patients - Anggie Stiexs; Kurniasari, Septi; Erwin, Tubagus; Nurhartanto, Adhi; Lestari, Ika; Agata, Annisa (Java Nursing Journal, 2026)
Background: Stroke remains a major cause of disability in Indonesia, and families provide essential care, yet evidence linking caregiver knowledge and caregiving behaviour to anxiety is limited Purpose: This study aimed to test associations between caregiver knowledge, caregiving behaviour, and anxiety among families of stroke patients. Methods: In a cross-sectional study at RSUD Abdul Moeloek, Indonesia (June 12, 2023), we enrolled 73 caregivers of stroke inpatients. Knowledge and behaviour were classified as good, fair, poor, and positive or negative. Anxiety was measured in categories. Associations were tested with chi-square. Results: Among 73 caregivers, knowledge was good in 21.9%, fair in 50.7%, and poor in 27.4%; 61.6% reported positive behaviour. Anxiety was reported sometimes by 8.2%, part of the time by 80.8%, and almost all of the time by 11.0%. Anxiety was associated with knowledge (p=0.023) and behaviour (p=0.001). Conclusion: Caregiver anxiety was frequent and significantly related to caregiver knowledge and behaviour. Findings support nurse-led screening plus structured education and skills coaching during inpatient care and discharge transitions. Relevance to clinical practice: Caregiver anxiety was common in families of hospitalised stroke patients and was linked to lower knowledge and negative caregiving behaviour. Nurse-led screening, teach-back education, and brief skills coaching (mobility, ADLs, medications, warning signs), followed by early follow-up, may reduce distress and strengthen safe transitional care